2001
DOI: 10.1557/proc-671-m3.3
|View full text |Cite
|
Sign up to set email alerts
|

Copper CMP for Dual Damascene Technology: Some Considerations on the Mechanism of Cu Removal

Abstract: It was found in a Cu-CMP process using EP-C 5001 slurry and IC 1000 pad that Cu removal rate, being extremely low without H2O2 in the slurry, increases up to a maximum with the addition of H2O2, and then decreases again. Analysis of polarization curves and Eh-pH diagrams shows that without H2O2 Cu has the lowest electric potential, as a result, the highest thermodynamic stability in the Cu/slurry system. Addition of H2O2 shifts the potential up and induces the formation of Cu2O, resulting in a high removal rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Insignificant differences with low levels of H 2 O 2 concentration at both pH levels may also be explained by the formation of Cu 2 O at high pH which is preferred for CMP compared to the CuO. This line of argument is supported by the report of Wei et al [5] who observed and measured the formation of Cu 2 O with the addition of 0.06%H 2 O 2 and the formation of CuO with the addition of 2.5% H 2 O 2 at a slurry pH of 8.…”
Section: A Removal Ratesupporting
confidence: 52%
See 2 more Smart Citations
“…Insignificant differences with low levels of H 2 O 2 concentration at both pH levels may also be explained by the formation of Cu 2 O at high pH which is preferred for CMP compared to the CuO. This line of argument is supported by the report of Wei et al [5] who observed and measured the formation of Cu 2 O with the addition of 0.06%H 2 O 2 and the formation of CuO with the addition of 2.5% H 2 O 2 at a slurry pH of 8.…”
Section: A Removal Ratesupporting
confidence: 52%
“…As mentioned earlier, slurry pH and the concentration levels of H 2 O 2 have been found to result in the formation of a hard passivation layer of CuO or Cu 2 O on the surface of the Cu [4,5]. In general, and in accordance with the Cu Pourbaix diagram [6], a number of studies have shown that surface chemistry in the basic region combined with a given peroxide concentration, can lead to the formation of CuO.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Copper is likely to replace tungsten in ULSI in the near future. There is a great deal of efforts to reveal the removal mechanism for copper polishing [29,33]. Similar to tungsten CMF, the surface passivation can also take place in copper CMF [29].…”
Section: Cmp In Ic Fabricationmentioning
confidence: 99%
“…Copper atoms are immediately oxidized in the slurry and CU20 remains. Further investigation on the removal mechanism of Cu CMF has been performed by Wei et al [33]. They demonstrated the material removal by pulling out the surface fragments bonded to the interacting oxygen atom.…”
Section: Cmp In Ic Fabricationmentioning
confidence: 99%